Melacak Pola Sebaran Riwayat Wafatnya Rasulullah SAW: Implementasi Studi Hadis Kawasan di Masa Periwayatan - M. Dede Rodliyana; Muhamad Ridwan Nurrohman (Diroyah : Jurnal Studi Ilmu Hadis, 2021)
The narrative of the death of the Prophet Muhammad is not just one. History in Sunni, He died in the lap of Aisha RA. While in the Shi'i narration, he died in the lap of Ali bin Abi Talib. These two narrations are also widespread in two conflicting Madrasas, Kufa (Shi'i) and Basra (nashibi). Thus, both camps can objectively narrate these two Hadiths. In this study, the author highlights the historical pattern of the narration of these two contradicting Hadiths to conclude the role of fanaticism in the spread of religious understanding, especially in the space of these hadiths. To solve the problem in question, the author uses content analysis with the al-ruwāt date approach. Due to the broad scope of discussion, in this paper, the author limits the conversation to the historical pattern of Aisyah RA. After research, it found that the history of Aisyah RA., which the author assumed w cut off in Kufa, is not so. It is just that there has been a refinement of narrating through narrating the hadith with meaning (al-Riwayah Bil Ma'na).